Online Marketing Strategies Used in the Promotion of Dietary Supplements in Romania - Briciu, Arabela; Briciu, Victor-Alexandru; Cogean, Claudiu Vasile; Gulpe, Ana-Maria (Springer, 2024)
The sale of dietary supplements in Romania has become increasingly important, competition is high and the online environment is an important channel for communication, promotion and sales. With the growth of online sales of dietary supplements, the increase in the number of users on social media platforms and mobile applications, there has been a significant increase in the number of companies that have chosen to promote their products online. Apart from that, there are other reasons for intensive online promotion: low cost, control and sorting of the target audience, analysis of the results, but also the lack of Romanian regulated legislation controlling online advertising of dietary supplements and especially on social media platforms. In this paper, we aim to identify the online marketing strategies used in the promotion of dietary supplements by five leading Romanian companies according to a study conducted in 2020 by the publication “Ziarul Financiar”, conducting a content analysis of how these companies promote themselves online and what strategies they use for this purpose. The data obtained from the analysis reveals that the online marketing tactics and strategies adopted are designed to increase the market visibility of dietary supplement companies, and that companies that develop strategies such as affiliate marketing, association with a virtual community or discussion group, etc., stand to gain. This approach and the results obtained can be helpful and relevant to specialists in the field.